2013
DOI: 10.3390/atmos4030254
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Extreme Precipitation Events Leading to Opposite Climate Change Signals over the Congo Basin

Abstract: Abstract:We investigate the reasons for the opposite climate change signals in precipitation between the regional climate model REMO and its driving earth system model MPI-ESM over the greater Congo region. Three REMO simulations following three RCP scenarios (RCP 2.6, RCP 4.5 and RCP 8.5) are conducted, and it is found that the opposite signals, with REMO showing a decrease and MPI-ESM an increase in the future precipitation, diverge strongly as we move from a less extreme to a more extreme scenario. It has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 30 publications
3
33
0
Order By: Relevance
“…In the central tropics (zone 3) the majority of the GCMs agree on an increase in annual total precipitation, whereas the RCM sub-ensemble indicates a decrease (even though some of the forcing model projections show a substantial increase in total rainfall). In a recent study by Saeed et al (2013) it is shown that the projected drying in the REMO RCM projections (which comprises the majority of the RCM sub-ensemble -see Table S1) is partly related to the depletion of soil moisture caused by high-intensity rainfall events, which leads on the long run to a less intense hydrological cycle over the region. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the central tropics (zone 3) the majority of the GCMs agree on an increase in annual total precipitation, whereas the RCM sub-ensemble indicates a decrease (even though some of the forcing model projections show a substantial increase in total rainfall). In a recent study by Saeed et al (2013) it is shown that the projected drying in the REMO RCM projections (which comprises the majority of the RCM sub-ensemble -see Table S1) is partly related to the depletion of soil moisture caused by high-intensity rainfall events, which leads on the long run to a less intense hydrological cycle over the region. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The global and regional model processes leading to the opposite precipitation signals of the regional and the global simulations in the projected climate over central Africa are presently investigated by Saeed et al [68]. They show that more frequent heavy precipitation events occur in REMO and lead to higher surface runoff than in the GCM.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, temperature increase is stronger in the regional simulations. The study of Saeed et al [68] refers the drier and warmer climate conditions projected by the regional model in central Africa to much more frequent heavy precipitation events and thus stronger surface runoff and less infiltration of water into the soil, leading to reduced local water recycling and less evaporative cooling in this region. If similar processes occur within the tropical climate types in South America and Indonesia, it will be investigated in following studies.…”
Section: Discussionmentioning
confidence: 99%
“…One aspect of the variability of particular interest is the oc- currence of heavy-precipitation events, which can result in flooding, affect disease incidence and reduce crop yields (IPCC, 2015). Changes in the frequency of these events can also affect trends in total precipitation due to non-linearity in land-surface processes (Saeed et al, 2013). Figure 7a shows the frequency distribution of daily-mean precipitation rates averaged over 2.5…”
Section: Tropical Rainfall Variabilitymentioning
confidence: 99%